Implementasi Pemakaian Komputer Interaktif Dengan Akhlak Pada Anak Usia Dini Di Lingkungan Kelurahan Kreo Selatan, Kecamatan Larangan Tangerang - Abdul Mufti; Adhi Susano; Aswin Fitriansyah (LPPM, 2017)
. Implementation of the use of interactive computer aimed at fortifying early childhood of the influence of technology is increasingly rapidly with the behavior of their morals are in accordance with the norms of public life in accordance with religious rules in the village of Kreo Selatan so as to have the computer skills can help create tranquility, and comfort in social life. While the intended target of this activity is the use of interactive computer without removing the behavior and morality in public life. The solution in overcoming the problem for early childhood to use a computer that morals are in accordance with the wishes of the user (user friendly) by providing information and motivation of the use of interactive computer in objective to follow religious norms, so that can provide stimulation to children who wants to use the computer.Keywords: Computer interactive, Early childhood, Morals